2021
DOI: 10.3390/v13091683
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Natural SARS-CoV-2 Infection in Lions (Panthera leo) at the Barcelona Zoo: Viral Dynamics and Host Responses

Abstract: To date, no evidence supports the fact that animals play a role in the epidemiology of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of the coronavirus infectious disease 2019 (COVID-19). However, several animal species are naturally susceptible to SARS-CoV-2 infection. Besides pets (cats, dogs, Syrian hamsters, and ferrets) and farm animals (minks), different zoo animal species have tested positive for SARS-CoV-2 (large felids and non-human primates). After the summer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 33 publications
4
70
0
2
Order By: Relevance
“…A replicating-virus neutralization assay of the Se2 sample was performed as previously described [15]. The inactivated serum sample was first diluted at 1:10 and then 2-fold serially diluted in DMEM.…”
Section: Sars-cov-2 Neutralization Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…A replicating-virus neutralization assay of the Se2 sample was performed as previously described [15]. The inactivated serum sample was first diluted at 1:10 and then 2-fold serially diluted in DMEM.…”
Section: Sars-cov-2 Neutralization Assaymentioning
confidence: 99%
“…Since the beginning of the pandemic, several domestic and wild animals have shown to be susceptible to SARS-CoV-2 infection [12,13]. Moreover, reverse zoonosis episodes have been documented on farms, in zoos and in familiar households [14][15][16][17]. Recently, by infecting wild-type mice, it has been shown that some SARS-CoV-2 variants display an increased virulence in humanized ACE2 transgenic mice and a broadened host range [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the spread of this virus among humans and many animals has been reported widely. These animals include domestic cats [23][24][25][26][27][28][51][52][53][54][55], dogs [23,26,28,52,54,55], and wild Felidae families, such as tigers [29,65,66], lions [29,[62][63][64], snow leopards [60,61] and cougars [59], as well as gorilla [91]. It was confirmed that the animals acquired viral infection from humans infected with SARS-CoV-2.…”
Section: Clinicalmentioning
confidence: 96%
“…In addition, there has been evidence of natural infections in various animals from several countries, including China, which was the first country in which human infections were found, and in other countries in Asia, Europe, Australia, Africa, and the Americas. Some studies conducted to challenge animals against SARS-CoV-2 infection are presented in Table-1 [22,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], whereas natural infections in animals, including domestic animals, farm animals, and wild animals, are listed in Table-2 [23][24][25][26][27][28][29]31,34,35,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66], and natural infections in the USA are listed in Table-3 . Experimental infections and natural cases with the presumed sources of infection and their transmission are summarized in Figure-1 [4,5,…”
Section: Sars-cov-2 Infections In Catsmentioning
confidence: 99%
“…The zoonotic potential adds another dimension in understanding the epidemiology of coronaviruses and successful surveillance. It is now known that SARS-CoV-2 can infect several wild and domestic animals [8][9][10]. However, the role of animals in the epidemiology of COVID-19 and the influence of SARS-CoV-2 on animal health have not been fully understood.…”
Section: Introductionmentioning
confidence: 99%